Clinicopathologic Features and Prognosis of BRAF Mutated Colorectal Cancer Patients - Guan, Wen-Long; Qiu, Miao-Zhen; He, Cai-Yun; Yang, Li-Qiong; Jin, Ying; Wang, Zhi-Qiang; Li, Yu-Hong; Xu, Rui-Hua; Wang, Feng-Hua (Frontiers in Oncology, 2020)
Background: BRAFV600E mutation is associated with poor prognosis of colorectal cancer (CRC) patients, but the comparison of clinic-pathologic features between V600E and non-V600E mutation was not well known in CRC patients. The aim of this study is to evaluate the clinical and pathological features, prognostic value of BRAF mutations in CRC. Methods: We conducted a retrospective study to characterize the clinical and pathological features and survival of patients with BRAF mutated CRC. Patients were classified according to BRAF status as BRAFV600E mutation and non-V600E mutations. Difference of characteristics and survival between the two groups was analyzed. Results: There was no significant difference in gender, family history, location of primary tumor, metastatic sites between patients with BRAF-V600E mutation and non-V600E mutations. Patients with V600E mutation were younger than those with non-V600E mutations (p=0.002). Patients with BRAFV600E mutation showed a poorer outcome than those with non-V600E mutations (23.1 vs 49.9 months, respectively, p=0.0024). Lack of CDX2 expression was associated with worse prognosis (mOS: 9.4m vs not reached, respectively, p=0.016). Status of V600E mutation did not affect the mPFS and ORR of first-line or second-line treatment. Conclusion: BRAFV600E mutation defines a distinct subgroup of CRC with worse prognosis. Lack of CDX2 expression is associated with poor OS. Status of V600E mutation did not affect the mPFS of first-line or second-line treatment.